Factors influencing the retention of entry level employees in the South African gaming industry. - Kgapola, Donald Kgope (My University, 2014)
ABSTRACT The increasingly competitive environment that organizations operate in has led to the realization that human capital is a pivotal factor in maintaining a competitive edge over your competitors, gaining market share and running a sustainable business. With this realization organizations are faced the challenge of retaining exceptional talent in the organization for as long as possible. The purpose of this study of this study is to identify and describe factors that influence entry level employee retention and determine their relative degree of importance to such employees. The study goes further, and tries to understand employee perception on how the organization is delivering currently on those factors. Utilizing a questionnaire-based survey which was circulated at Montecasino amongst entry level employees within its three main departments, respondents were requested to complete it in order to reach a conclusion on what they perceive as important, and how well the organization delivers on those factors. The study found that the most important factor to entry level employees is organizational justice and that the organization delivers best on providing advancement opportunities. The difference between the degrees of importance amongst these factors was found to not be vastly different as they all had a positive influence towards retention. Entry level employees wish to be treated and rewarded fairly by their organization and in return they would be more committed to the organization. They perceive the organization to be delivering poorly on what they see as most important to them. However, the organization delivers fairly on providing advancement opportunities and job satisfaction. The relationship between these factors is significant in that negative delivery on one affects the way others are perceived. For the organization to succeed in retaining these entry level employees, it would have to ensure the alignment between these important retention factors and their effective delivery.
MBA 2014
Keywords: Employee retention,Gambling industry.